1978
DOI: 10.1042/bj1740741
|View full text |Cite
|
Sign up to set email alerts
|

Activity and androgenic control of enzymes associated with the tricarboxylic acid cycle, lipid oxidation and mitochondrial shuttles in the epididymis and epididymal spermatozoa of the rat

Abstract: 1. Enzyme activities (units/g wet wt.) were determined in the caput and cauda epididymidis and in epididy'mal spermatozoa of the rat. 2. The activity of most enzymes in the cauda was between 5d and 100 % of that in the caput, except that'ATP citrate lyase was barely detectable in the cauda. 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 54 publications
4
24
1
Order By: Relevance
“…Effect of a-bromohydrin phosphate on the concentration of (a) dihydroxyacetone phosphate (DHAP) (n = 8) and (b) fructose-1,6-bisphosphate (F-l,6-P2) ( Cooney, 1987, Cooney andJones, 1988), or 3-bromopyruvate, which inhibits glyceraldehyde 3-phosphate dehydrogenase and 3-phosphoglycerate kinase , also prevented the production of C02, resulted in an increase in concen¬ trations of dihydroxyacetone phosphate and fructose-1,6-bisphosphate, but had no appreciable effect on the (Voet and Voet, 1995); the former is located in the cytoplasm whereas the latter is bound to the inner mitochondrial membrane (Klingenberg and Bucholz, 1970 These results confirm those of Ford (1981) that, in boar spermatozoa, glycerol 3-phosphate is oxidized primarily by an FAD-dependent dehydrogenase that is probably extrinsically bound to the inner mitochondrial membrane (Klingenberg and Bucholz, 1970). In this respect, boar spermatozoa are similar to those of rams (Ford, 1981), rats (Ford, 1981;Brooks, 1978;Schenkman et al, 1965) and cocks (Yamada and Terada, 1974) but not those of mice (Burgos et al, 1982) or humans (Ford, 1981). The ability of a-bromohydrin phosphate to inhibit this enzyme in boar spermatozoa is probably due to the R-isomer which has identical stereochemistry to the normal substrate (S)-(or sn·) glycerol 3-phosphate.…”
Section: Introductionsupporting
confidence: 78%
“…Effect of a-bromohydrin phosphate on the concentration of (a) dihydroxyacetone phosphate (DHAP) (n = 8) and (b) fructose-1,6-bisphosphate (F-l,6-P2) ( Cooney, 1987, Cooney andJones, 1988), or 3-bromopyruvate, which inhibits glyceraldehyde 3-phosphate dehydrogenase and 3-phosphoglycerate kinase , also prevented the production of C02, resulted in an increase in concen¬ trations of dihydroxyacetone phosphate and fructose-1,6-bisphosphate, but had no appreciable effect on the (Voet and Voet, 1995); the former is located in the cytoplasm whereas the latter is bound to the inner mitochondrial membrane (Klingenberg and Bucholz, 1970 These results confirm those of Ford (1981) that, in boar spermatozoa, glycerol 3-phosphate is oxidized primarily by an FAD-dependent dehydrogenase that is probably extrinsically bound to the inner mitochondrial membrane (Klingenberg and Bucholz, 1970). In this respect, boar spermatozoa are similar to those of rams (Ford, 1981), rats (Ford, 1981;Brooks, 1978;Schenkman et al, 1965) and cocks (Yamada and Terada, 1974) but not those of mice (Burgos et al, 1982) or humans (Ford, 1981). The ability of a-bromohydrin phosphate to inhibit this enzyme in boar spermatozoa is probably due to the R-isomer which has identical stereochemistry to the normal substrate (S)-(or sn·) glycerol 3-phosphate.…”
Section: Introductionsupporting
confidence: 78%
“…However, nothing is known about the molecular identity of this epididymis-specific form. The enzymes citrate synthase, malate dehydrogenase and carnitine acetyl transferase have been reported at higher levels in epididymal sperm and also indicated to be androgen dependent with the exception of malate dehydrogenase (Marquis & Fritz 1965, Brooks 1978.…”
Section: Discussionmentioning
confidence: 99%
“…ADT4 (Kim et al 2007), VDAC2 (Hinsch et al 2004), GAPDHS (Westhoff & Kamp 1997), hexokinase HK1 (Mori et al 1998, Travis et al 1998, AKAP4 (Turner et al 2001), dihydrolipoamide dehydrogenase acetyl transferase (Mitra et al 2005), carnitine acetyl transferase (Jeulin & Lewin 1996), 3-oxoacid CoA transferase (Koga et al 2000), tektin 3 (TEKT3; Wolkowicz et al 2002) (Brooks 1978), VDAC3 (Hinsch et al 2004), prohibitin (Thompson et al 2003), SMCP (Herr et al 1999), GPX4 (Nagdas et al 2005), have been reported earlier and were found to be present in testis and epididymis/ ejaculated sperm. The proteins ADT4 (Kim et al 2007) and VDAC2 (Hinsch et al 2004) have not been reported on head domain earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa are well known to have the ability to oxidize glycerol (Mann & White, 1957;White, 1957) via the activity of glycerol kinase (Mohri & Masaki, 1967) and flavin-linked glycerolphosphate dehydrogenase (Mohri, Mohri & Ernster, 1965;Schenkman, Richert & Westerfeld, 1965;Brooks, 1978 (Crabo & Appelgren, 1972;Edwards, Jones & Waites, 1975), it is highly likely that the accumulated material is not unchanged -chlorohydrin, but a dechlorinated product (Edwards et al, 1975; . R. Jones, personal communication), and so spermatozoa in the cauda epididymidis may not be exposed to high concentrations of a-chlorohydrin.…”
Section: Discussionmentioning
confidence: 99%
“…NAD-linked glycerolphosphate dehydrogenase (EC 1.1.1.8) was assayed in the forward direction in a medium containing 180 mM-glycine, 3-8 M-hydrazine hydrate, 1 mM-NAD+, pH 9-8, and the reaction was initiated by adding various concentrations of D,L-glycerol 3-phosphate. Flavin-linked glycerolphosphate dehydrogenase (EC 1.1.99.5) was assayed as described by Brooks (1978).…”
Section: Introductionmentioning
confidence: 99%